Increased risk of smoking and pain in individuals with intermittent explosive disorder in the All of Us dataset - Ralston, Fiona; Thomas, Michael L.; Stein, Murray B.; Coccaro, Emil F.; Meruelo, Alejandro D. (Frontiers in Psychiatry, 2025)
IntroductionIntermittent Explosive Disorder (IED) is characterized by recurrent impulsive aggression and has been linked to impairments in physical and psychological functioning. However, population-based evidence examining health-related correlates of IED remains limited. This study evaluated whether individuals with IED differ from matched controls in tobacco use and pain, two clinically relevant health domains.MethodsData were drawn from the All of Us Research Program. Individuals with IED were matched 10:1 to participants without IED based on age, sex, race/ethnicity, and income. Group differences in tobacco use and pain were examined using chi-square analyses and logistic regression. Models estimated odds ratios (ORs) with 95% confidence intervals (CIs), with multivariable models additionally adjusting for major depressive disorder (MDD) and generalized anxiety disorder (GAD).ResultsRelative to matched controls, individuals with IED showed significantly higher odds of lifetime cigarette smoking, and this association remained robust after adjusting for MDD and GAD. Participants with IED also demonstrated significantly greater odds of reporting moderate to severe pain during the past seven days.DiscussionFindings suggest that IED is associated with elevated vulnerability to both smoking and pain, independent of co-occurring depressive and anxiety disorders. These results highlight the importance of integrating tobacco cessation and pain management strategies into clinical care for individuals with IED and underscore the value of large-scale biobank data in clarifying health risks associated with psychiatric disorders.